ANALYSIS OF TEACHER KNOWLEDGE ABOUT EARLY CHILD SEX EDUCATION VIEWED FROM THE BACKGROUND OF TEACHER EDUCATION IN MEDAN - Raniyah, Qaulan (Proceeding International Seminar of Islamic Studies, 2023)
Cases of violence and sexual harassment that occur in early childhood in various regions are due to the lack of sex education being taught to children. Family and teachers as the closest environment must provide knowledge about sex education to children. However, there are still many teachers who do not understand the right sex education to be taught in early childhood. This study aims to see the extent of teachers' knowledge of early childhood sex education. This study used a qualitative descriptive analysis method, on teachers in 42 ABA Kindergartens throughout Medan City. The results showed that the various educational backgrounds of PAUD teachers influenced the level of knowledge of sex education in children. Teachers with a bachelor's degree in early childhood education have better knowledge of early childhood sex education than teachers with other educational backgrounds